Model Kinetika Produksi Biogas dari Limbah Makanan - Shitophyta, Lukhi Mulia (Fakultas Teknik, Universitas Brawijaya, 2020)
Biogas is one of the renewable energies to minimize the use of fossil fuels. Biogas can be generated from food wastes through anaerobic digestion. The study aimed to determine the kinetic model of biogas production from food waste using linear, exponential and Gaussian equations. The result showed that the simulation of the Gaussian equation (R2 0.992) is the ideal model to be applied to a kinetic model of biogas production from food waste, while the exponential equation had the greater value of R2 than linear equation.